The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0017896919836132
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition literacy is associated with healthy-eating behaviour among college students in Taiwan

Abstract: Objective: This study aimed to investigate the nutrition literacy status of Taiwanese college students and to assess the relationship between nutrition literacy and healthy-eating behaviours. Design: Cross-sectional design with convenience sampling. Setting: Six universities in northern, central and southern Taiwan; both national and private universities were included in each region. Method: A maximum of 220 students was recruited from each university with no more than 45 students from one department. Data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 42 publications
8
49
0
5
Order By: Relevance
“…Meeting the results obtained in the present analysis, another Portuguese study found that approximately half of its sample demonstrated a good and higher degree of NL [16]. This can be explained by the fact that, nowadays, people, especially those of younger ages, find it easier to access the internet and, consequently, find it easier to seek information about nutrition and healthy habits [17]. Furthermore, a study in Iran found that nutrition knowledge was lower in participants from areas other than health sciences, such as, for example, participants in the area of business administration [18].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Meeting the results obtained in the present analysis, another Portuguese study found that approximately half of its sample demonstrated a good and higher degree of NL [16]. This can be explained by the fact that, nowadays, people, especially those of younger ages, find it easier to access the internet and, consequently, find it easier to seek information about nutrition and healthy habits [17]. Furthermore, a study in Iran found that nutrition knowledge was lower in participants from areas other than health sciences, such as, for example, participants in the area of business administration [18].…”
Section: Discussionsupporting
confidence: 79%
“…Drichoutis and colleagues also corroborate this information, reporting that individuals who do not obtain nutritional formation through specialties, such as nutritionists and dietitians, have less nutritional knowledge [ 20 ]. This is because, in courses and jobs related to health sciences, mainly nutrition and dietetics, topics like nutrition, healthy eating, and correct eating habits are regularly addressed, as well as the people who are accompanied by these professionals [ 17 ]. Contrary to what was obtained in the present analysis, several studies did not observe statistically significant differences between the level of NL and BMI, suggesting that there may exist other factors than nutrition knowledge influencing BMI [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature indicates that NL is significantly related to sociodemographic variables and healthy eating behavior [28,[36][37][38][39]. Many scholars have used the social-ecological model to identify multi-level factors that affect healthy eating behavior [14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that health literacy mediated the relationship between sociodemographic variables and health-promoting behaviors/health outcomes [33][34][35]. Since NL is associated with healthy eating behavior and derived from health literacy [28,[36][37][38], and sociodemographic variables are also predictors of NL [38,39], we assume that NL may play a similar role to health literacy in mediating the effect of factors influencing healthy eating on healthy eating behavior.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation